Unruptured tubal pregnancy: different treatments for early and late diagnosis - Elito Junior, Julio; Camano, Luiz (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: There is evidence that ectopic pregnancies present different behavioral patterns. These distinct evolutions of ectopic pregnancies represent two different natural histories. To evaluate these evolution patterns, we compared patients undergoing medical treatment and expectant management according to their gestational age and initial beta-hCG levels. DESIGN AND SETTING: Prospective study at the Department of Obstetrics of Universidade Federal de São Paulo, a tertiary center. METHODS: Among 119 cases of unruptured ectopic pregnancies diagnosed from April 1999 to February 2004, 57 received systemic treatment with methotrexate 50 mg/m2 (body surface area) intramuscularly and 62 were managed expectantly. In this study we evalu- ated the beta-hCG levels at presentation and amenorrhea duration. RESULTS: There was a significant difference between the two groups regarding amenorrhea duration and initial beta-hCG levels (p < 0.001). The group with decreasing beta-hCG levels (man- aged expectantly) had longer amenorrhea (mean: 8.87 ± 1.71 weeks) and lower initial beta-hCG levels (mean: 648.8 ± 754.7 mIU/ml). On the other hand, the group treated with methotrexate had shorter amenorrhea (mean: 6.81 ± 1.88 weeks) and higher beta-hCG levels at presentation (2642.7 ± 2315.1 mIU/ml). CONCLUSIONS: The data suggest that ectopic pregnancies can be categorized into two groups: those with early diagnosis and shorter amenorrhea, increasing or maintained beta-hCG levels over 24 and 48-hour intervals and higher beta-hCG levels requiring medical treatment; and those with late diagnosis and longer amenorrhea, decreased beta-hCG levels over 24 and 48 hour intervals and lower beta-hCG levels requiring expectant management.